Destructive adsorption of methyl parathion over nanocrystalline MgO - Reddy, V. S.; RadheShyam, A.; Dwivedi, Reena; Gupta, R. K.; Chumbhale, Vilas R.; Prasad, R. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2005)
Destructive adsorption of methyl parathion (MP) has been investigated over few transition metal oxides and alkali earth metal oxides. Performance of alkaline earth oxides have been found to be better than transition metal oxides and best performance has been shown by aerogel method prepared nanocrystalline AP-MgO. The AP-MgO powder has been characterized by XRD, AFM and BET surface area measurements. Destructive adsorption of MP over AP-MgO has been compared with that of activated carbon. Both are found to adsorb methyl parathion effectively. An IR investigation of the surface of treated AP-MgO and activated carbon reveals that activated carbon adsorbs methyl parathion as such in the molecular form and AP-MgO adsorbs it destructively.